Translocatable resistance to mercuric and phenylmercuric ions in soil bacteria. - Radford, A J (1981)
Of a sample of 42 gram-negative Hg-resistant bacteria, three (a Pseudomonas fluorescens, a Klebsiella sp. and a Citrobacter sp.) contained translocatable elements conferring resistance to Hg2+ (all three) and to Hg2+ and phenylmercuric acetate (P. fluorescens). The discovery of transposable phenylmercuric acetate resistance extends the range of known resistance "transposons" from heavy metals and antibiotics to organometallic compounds.